Gender-Specific Related Factors for Suicidal Ideation During COVID-19 Pandemic Lockdown Among 5,175 Chinese Adolescents - Jin Zhu; Jin Zhu; Jin Zhu; Jin Zhu; Baohua Li; Fengcheng Hao; Linlin Luo; Linlin Luo; Song Yue; Song Yue; Jinguo Zhai; Jinguo Zhai; et al. (Frontiers Media S.A., 2022)
BackgroundSuicide was an urgent issue during the pandemic period in adolescents. However, few studies were focused on suicide during the coronavirus disease 2019 (COVID-19) pandemic lockdown.MethodsAn online survey was conducted among 5,175 Chinese adolescents from June 9th to 29th in 2020 to investigate the prevalence of suicidal ideation (SI) during COVID-19 pandemic lockdown. A gender-specific stepwise logistic regression model was used. All analyses were performed with STATA 15.0.ResultsAbout 3% of the participants had reported having SI during the COVID-19 pandemic lockdown period. The prevalence of female SI (3.64%, 95% CI: 2.97-4.45%) was higher than that of males (2.39%, 95% CI: 1.88-3.05%) (χ2 = 6.87, p = 0.009). Quarreling with parents [odds ratio (OR) = 9.73, 95% CI: 5.38-17.59], insomnia (OR = 5.28, 95% CI: 2.81-9.93), previous suicide attempt history (OR = 3.68, 95% CI: 1.69-8.03), previous SI history (OR = 2.81, 95% CI: 1.30-6.06), and feeling depressed during pandemic lockdown (OR = 2.26, 95% CI: 1.22-4.18) were positively associated with the males' SI. However, having emptiness inside (OR = 4.39, 95% CI: 2.19-8.79), quarreling with parents (OR = 3.72, 95% CI: 2.16-6.41), insomnia (OR = 3.28, 95% CI: 1.85-5.80), feeling anxious (OR = 2.62, 95% CI: 1.46-4.70), and longing for father's emotional warmth (OR = 0.38, 0.20-0.72) were associated mostly with females' SI.ConclusionsFemale adolescents, who felt emptiness from their families and their fathers' emotional warmth, were at much higher risk of having SI during COVID-19 lockdown. We must specify a suicide prevention policy and interventions for adolescents in the pandemic crisis based on gender gaps.